2022
DOI: 10.3389/fimmu.2022.850540
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GAD65 Antibody-Associated Autoimmune Encephalitis With Predominant Cerebellar Involvement Following Toripalimab Treatment: A Case Report of a Novel irAE of Toripalimab

Abstract: Toripalimab (Junshi Bioscience Co., Ltd) is a new immune checkpoint inhibitor (ICI) that targets programmed cell death protein 1 (PD-1) in various cancers, including metastatic melanoma. No neurological immune-related adverse events (n-irAEs) of toripalimab have been reported, except for neuromuscular involvement. We report a case of a 63-year-old woman who presented with severe vertigo, vomiting, nystagmus, cerebellar ataxia, and cognitive impairment after toripalimab treatment for metastatic melanoma. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Therefore, she was diagnosed with toripalimab-related n-irAE accompanied with multiple demyelinating imaging changes, in combination with asymptomatic myocarditis and hypothyroidism. This n-irAE displayed a different timing of onset as well as the symptoms and we found that intracranial imaging changed markedly compared to the case of early-onset cognitive dysfunction along with overt signs and symptoms of cerebellar involvement as reported earlier by Zhou et al [ 22 ]. In an analysis of 347 patients treated with pembrolizumab or nivolumab, the median time to onset of n-irAEs was 5.5 cycles.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, she was diagnosed with toripalimab-related n-irAE accompanied with multiple demyelinating imaging changes, in combination with asymptomatic myocarditis and hypothyroidism. This n-irAE displayed a different timing of onset as well as the symptoms and we found that intracranial imaging changed markedly compared to the case of early-onset cognitive dysfunction along with overt signs and symptoms of cerebellar involvement as reported earlier by Zhou et al [ 22 ]. In an analysis of 347 patients treated with pembrolizumab or nivolumab, the median time to onset of n-irAEs was 5.5 cycles.…”
Section: Discussionsupporting
confidence: 68%
“…Encephalitis is a common adverse reaction of the nervous system and has been reported to be associated with PD-1 inhibitor immunotherapy in the clinic ( Williams et al, 2016 ). Patients often have elevated levels of autoantibodies, but lack specificity, such as Anti-Hu ( Papadopoulos et al, 2018 ), Anti-PCA-2 ( Segal et al, 2022 ), Anti-GAD65 ( Chung et al, 2020 ; Zhou et al, 2022 ) and Anti-Glial fibrillary acidic protein (GFAP; Kapadia et al, 2020 ). When diagnosing CNS encephalitis, it is necessary to differentiate it from paraneoplastic neurological diseases (PNS) by excluding infectious diseases, tumor metastasis, etc., and distinguishing it based on the time of onset of encephalitis symptoms, whether they appear after PD-1 treatment, and the effectiveness of immunosuppressive therapy.…”
Section: Common Symptoms Of Naementioning
confidence: 99%
“…Ocular motor abnormalities have also been rarely described during treatment with ICIs [9][10][11], including vertical or horizontal nystagmus associated with acute cerebellar ataxia or brainstem encephalitis.…”
Section: Introductionmentioning
confidence: 99%